2019
DOI: 10.1021/acssensors.9b00946
|View full text |Cite
|
Sign up to set email alerts
|

Dark-Field Microwells toward High-Throughput Direct miRNA Sensing with Gold Nanoparticles

Abstract: MicroRNA (miRNA) is a class of short RNA that is emerging as an ideal biomarker, as its expression level has been found to correlate with different types of diseases including diabetes and cancer. The detection of miRNA is highly beneficial for early diagnostics and disease monitoring. However, miRNA sensing remains difficult because of its small size and low expression levels. Common techniques such as quantitative real-time polymerase chain reaction (qRT-PCR), in situ hybridization and Northern blotting have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…In this way, miRNA-21 could be detected with a proportional band from 1 fM to 100 pM, as well as a LOD of 0.60 fM which is much lower than previous reports [ 46 ]. Through applying dark-field microwells and 50 nm AuNPs that functionalized with DNA, Hwu et al [ 47 ] also presented a new tool for the detection of miRNA in buffer solution as well as cell lysate. Without involving a dark-field microscope, this miniaturized device enables the readout of an AuNP assay.…”
Section: Plasmonic Gold Nanostructures For Biosensing In Vitromentioning
confidence: 99%
“…In this way, miRNA-21 could be detected with a proportional band from 1 fM to 100 pM, as well as a LOD of 0.60 fM which is much lower than previous reports [ 46 ]. Through applying dark-field microwells and 50 nm AuNPs that functionalized with DNA, Hwu et al [ 47 ] also presented a new tool for the detection of miRNA in buffer solution as well as cell lysate. Without involving a dark-field microscope, this miniaturized device enables the readout of an AuNP assay.…”
Section: Plasmonic Gold Nanostructures For Biosensing In Vitromentioning
confidence: 99%
“…Therefore, Hwu and coworkers reported a new tool based on dark‐field microwells, which was a miniaturized dark‐field setup with multiplex capability and a simple camera read‐out, for the detection of microRNAs (miRNAs) in parallel at a high throughput. [ 159 ] Although the plasmon coupling contributes a distinct change in the scattering light of PNPs, it is difficult to discriminate the aggregation state of PNPs. For example, the addition of target nucleic acids results in the generation of both PNP dimmers and PNP clusters containing more than 2 single particles, and the identification of nanoparticle dimmers is ultimately relied on experience.…”
Section: Single Plasmonic Nanoprobes In Nucleic Acid Detectionmentioning
confidence: 99%
“…Probing singular biological entities will enhance our understanding of cell-to-cell variations in a given heterogeneous population. Recently, for rapid and accurate point-of-care testing of single cell (bacterial, human), several studies reported the use of plasmonic arrays (Zopf et al, 2019), doped NPs (Alafeef, Dighe, & Pan, 2019), micro-wells with plasmonic assays (Hwu et al, 2019), and integrated plasmonic NPs-peptide platforms (J. Zhou et al, 2014).…”
Section: Interactions Of Light With Biological Mattersmentioning
confidence: 99%
“…Probing singular biological entities will enhance our understanding of cell‐to‐cell variations in a given heterogeneous population. Recently, for rapid and accurate point‐of‐care testing of single cell (bacterial, human), several studies reported the use of plasmonic arrays (Zopf et al, 2019), doped NPs (Alafeef, Dighe, & Pan, 2019), micro‐wells with plasmonic assays (Hwu et al, 2019), and integrated plasmonic NPs‐peptide platforms (J. Zhou et al, 2014). The sensing bead techniques/methods reported in all these studies are limited by the extremely small volumes tested and involve complex setups to manufacture the sensors including lithography systems, nanomaterial synthesis, and chemical vapor deposition systems.…”
Section: Biological Applications Of Hsimentioning
confidence: 99%